Aspectos regionais da inovação verde e da internacionalização: Um estudo em empresas brasileiras - Oliveira, Jéssica Izidoro Custódia (2023)
Globalization and advances in technology have favored the growth of trade and investment between countries. In this sense, internationalization has been used as an alternative for the growth of companies, as well as an opportunity for their returns to be leveraged from operations in foreign markets. Green innovation has been recognized as one of the main factors that affect financial growth, environmental sustainability and quality of life, where innovation networks emerge as a strategy or instrument for regional development. In the literature, some studies are found, directly or indirectly addressing green innovation and its importance, but which still timidly approach the theme related to internationalization. Therefore, this study analyzed the relationship between the process of internationalization and green innovation of exporting companies in promoting competitive advantages and expected benefits through partnerships with public authorities and third sector organizations. The research sample consisted of 122 exporting companies from Uberlândia and Ribeirão Preto, provided by the “Lists of Exporting and Importing Companies”, made available by the Foreign Trade Secretariat (SECEX), between the years 2019 to 2021. As a methodology, this This work was characterized by being a descriptive study, with a quantitative approach, since data were collected and Structural Equation Modeling was used to analyze the relationship between the variables. The main results of the work were: (a) the internationalization process is positively related to the adoption of Green Product Innovation practices, Green Processes, Green Innovation and Green Innovation Behaviors of companies; (b) Green Product Innovation (GPI) and Green Innovation (GIP) practices positively impact the competitive advantage (VANT COMP) of companies. In addition, Green Innovation (PIV) practices promote expected benefits (BE) for exporting companies in Uberlândia and Ribeirão Preto, confirming that green innovation can positively benefit organizations; (c) the Green Innovation Behavior (GIC) manages to provide expected benefits (BE) to companies in a moderate way. Regarding the Competitive Advantage (VANT COMP) provided by the companies' Green Innovation, the results showed that only the Green Product Innovation (IPV) and the Green Innovation Practices (PIV) positively impact the companies' competitive advantage; (d) regarding the Expected Benefits (BE) with Green Innovation, the results show that Green Product Innovation (IPV) and Green Process Innovation (IPrV) do not provide benefits to companies such as profitability and greater market share nor for society as partnerships with local government. These conclusions suggest that although there are some limitations regarding the expected benefits and competitive advantages provided by Green Innovation to companies, the internationalization process is positively aligned with Green Innovation practices, meeting SDGs 8, 9 and 17 of the Agenda 2030. Thus, through this research it became evident that, with organizations increasingly engaged in promoting sustainable actions, aspects such as improving the quality of life, preserving biodiversity and natural resources, reducing social inequality and improving economy due to eco-efficiency, tend to be increasingly present, thus generating a balance in the social, economic and environmental spheres.